Identificação e gestão de competências em coordenadores de projetos de edificações : um estudo exploratório - Sabrina Santos Marins (2018)
The increasing demand on quality and performance assurance in buildings, added to the complexity of projects and the pressure to reduce costs, have been factors inducing a process of project coordination valorization. This coordination acquires different roles and responsibilities depending on the different companies and agents involved, ranging from project compatibilization to more strategic managerial functions. In this context, the research rescues a relatively unexplored topic, which is competence management by project coordinators in the construction industry. This work presents two questions as research problems: on one hand, what competences are associated to the different functions of project coordination and how they can be classified; on the other hand, how these competences are acquired and developed, and in particular whether it is possible to assess the role of continuing and post-graduation education in the acquisition and development of these skills. The research method follows the structure of similar works: systematic literature review, conduction of semi-structured interviews, focus group discussion, debate discussion, survey research and data triangulation. Results point to the fact that the combination of different learning experiences is what enriches the acquisition and development of appropriate competences, and it is not possible to affirm that there is a better path for development. Formal education is presented as a resource for competence improvement while its acquisition and development occur with its greatest significance in the work environment and/or by a vigorous individual and introspective effort. Therefore, it appears that improvement methods designed to include systematic inquiry, reflection and sharing of results can promote the intensification of learning just as innovative approaches may allow the intensification of competence development in formal education.